Dosis Kompos Tandan Kosong Kelapa Sawit (TKKS) Ber-Bakteri Selulolitik terhadap Pertumbuhan Jagung (Zea mays L.) di Tanah Ultisol: Dosage of Empty Palm Oil Bunches Compost with Cellulolytic Bacteria on Corn (Zea Mays L.) Growth in Ultisol Soil - Gusmawartati; Randi Ardinsyah (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
This research aims to utilize Ultisol soil in increasing the growth and production of corn by improving the constraints on Ultisol soil, one of which is low pH and low organic matter. Application of compost for oil palm empty fruit bunches with cellulolytic bacteria is an alternative to improve the problem of Ultisol soil. This research was carried out in the experimental garden of the Faculty of Agriculture, Riau University from November 2020 to March 2021. This research was conducted experimentally used a non-factorial experiment with 4 replications. Application of oil palm empty fruit bunches compost with cellulolytic bacteria as follows: T0 = 0 t.ha-1, T1 = 5 t.ha-1, T2 = 10 t.ha-1, T3 = 15 t.ha-1, T4 = 20 t.ha-1. The results of this research indicate that the application of 20 t.ha-1 couldgive a significant effect on each parameter such as plant height, male flower appearance, female flower appearance and plant dry weight. Based on the results of the research, it is recommended to use oil palm empty fruit bunches compost with cellulolytic bacteria at a dose of 20 t.ha-1 to get optimal results.